2012
DOI: 10.1074/jbc.m112.351999
|View full text |Cite
|
Sign up to set email alerts
|

Apicomplexan Parasite, Eimeria falciformis, Co-opts Host Tryptophan Catabolism for Life Cycle Progression in Mouse

Abstract: Background:The kynurenine pathway catalyzes tryptophan catabolism in mammals. Results: The rate-limiting indoleamine 2,3-dioxygenase and two other enzymes of the host kynurenine pathway are required for an efficient development of the apicomplexan parasite E. falciformis in mouse. Conclusion: A previously unanticipated pro-parasite function of host tryptophan catabolism is revealed. Significance: An intracellular pathogen subverts the host defense (IFN␥, IDO1) for progression of natural life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…falciformis BayerHaberkorn1970 (Haberkorn, 1970) Between the two E. falciformis isolates BayerHaberkorn1970 and Brandenburg88 we observed only slight differences in the length of the pre-patent period (time until oocyst shedding, starting at 6 vs. 7 dpi). These results are in agreement with previous reports from the same host (NMRI mice) and the BayerHaberkorn1970 isolate (Stange et al, 2012;Schmid et al, 2012Schmid et al, , 2014Ehret et al, 2017). The pre-patent period for the wild derived E. falciformis isolate (7 dpi) corresponds to that reported for the parasite isolate E. falciformis var praghensis (Mesfin et al, 1978;Kasai et al, 1991), but Mahrt and Shi (1988) and Schito et al (1996) demonstrated slightly longer pre-patent periods (7 or 8 dpi) also in other E. falciformis infections.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…falciformis BayerHaberkorn1970 (Haberkorn, 1970) Between the two E. falciformis isolates BayerHaberkorn1970 and Brandenburg88 we observed only slight differences in the length of the pre-patent period (time until oocyst shedding, starting at 6 vs. 7 dpi). These results are in agreement with previous reports from the same host (NMRI mice) and the BayerHaberkorn1970 isolate (Stange et al, 2012;Schmid et al, 2012Schmid et al, , 2014Ehret et al, 2017). The pre-patent period for the wild derived E. falciformis isolate (7 dpi) corresponds to that reported for the parasite isolate E. falciformis var praghensis (Mesfin et al, 1978;Kasai et al, 1991), but Mahrt and Shi (1988) and Schito et al (1996) demonstrated slightly longer pre-patent periods (7 or 8 dpi) also in other E. falciformis infections.…”
Section: Discussionsupporting
confidence: 94%
“…The isolate E. falciformis BayerHaberkorn1970 has been isolated in 1960 (Haberkorn 1970) and since has been propagated in laboratories (first at Bayer animal health, Monheim, Germany; then at the institute for molecular parasitology of the Humboldt University, Berlin, Germany). In nearly 60 years since its isolation E. falciformis BayerHaberkorn1970 has likely become the most commonly used laboratory isolate of rodent Eimeria (Mahrt and Shi 1988;Schito et al, 1996;Steinfelder et al, 2005;Pogonka et al, 2010;Stange et al, 2012;Schmid et al, 2014Schmid et al, , 2012Ehret et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, infection of mice with the roundworm Trichuris muris (a model of the human intestinal disease trichuriasis) induces IDO1 in goblet cells of the caecum of immune-deficient SCID (severe combined immunodeficiency) mice and studies with 1-MT provided evidence that IDO1 lowers the turnover rate of colonic epithelial cells, allowing the parasite to persist at the base of the caecal crypts [509]. Eimeria falciformis, which infects mouse intestinal epithelial cells, also takes advantage of IDO1 expression within the host; infection with this parasite induces IDO1 in the caecal epithelium, resulting in the formation of xanthurenic acid that is necessary for normal E. falciformis development [510]. In contrast, other Kyn pathway metabolites can suppress parasite function in vitro, e.g.…”
Section: Parasitesmentioning
confidence: 99%
“…The sequences of human and mouse IDO-2 show a similarity of approximately 43% to human and mouse IDO-1, respectively, which results in distinct substrate ranges and kinetic activities, different selectivities toward some inhibitors, and distinct expression patterns with regard to tissues and stimuli, which make a complete functional redundancy of IDO-1 and IDO-2 unlikely (13-16). While IDO-1 is encoded only by the genomes of mammals, IDO-2 can also be found in lower vertebrates (14).IDO-1 is not constitutively expressed but requires stimulation by host-and pathogen-derived inflammatory molecules such as proinflammatory cytokines (gamma interferon [IFN-␥], tumor necrosis factor [TNF]) and Toll-like receptor ligands (17), a regulation that functions as part of an immune response to pathological conditions such as protozoan infections (9,18,19). High levels of expression of IDO-1 lead to Trp depletion and increased levels of downstream neuroactive kynurenine metabolites (20).…”
mentioning
confidence: 99%
“…IDO-1 is not constitutively expressed but requires stimulation by host-and pathogen-derived inflammatory molecules such as proinflammatory cytokines (gamma interferon [IFN-␥], tumor necrosis factor [TNF]) and Toll-like receptor ligands (17), a regulation that functions as part of an immune response to pathological conditions such as protozoan infections (9,18,19). High levels of expression of IDO-1 lead to Trp depletion and increased levels of downstream neuroactive kynurenine metabolites (20).…”
mentioning
confidence: 99%